Amphibian Conservation and Traditional Health Practices: Insights from the Buffer Zone of Bukit Barisan Selatan National Park, Lampung, Indonesia - Dewi, Bainah Sari; Harianto, Sugeng Prayitna; Al Ikhsan, Ahmad; Wibowo, Novita; Fadhila, Safira Cahya; Tokita, Norio; Iwai, Noriko (JSW (Jurnal Sosiologi Walisongo), 2024)
Cultural practices surrounding traditional medicine using amphibians in Indonesia are practices that can be found in several regions with diverse contexts. In the buffer zone of Bukit Barisan Selatan National Park, this practice is found with diversity among residents near and far from the buffer zone. With an orientation towards highlighting their significance to community health and social life, this research focuses on the local knowledge system regarding health and healing. Applying qualitative research uses informant s as data source. and the data collecting uses interviews, the findings of this study show that the local knowledge system regarding amphibians is as a food and medicinal material. Knowledge systems are determined by people's knowledge and involvement with the work they do. The impact of the knowledge system about the benefits of amphibians has implications for the attitudes of local residents towards amphibians and the environment in which they live. The implications of this knowledge system among  local  community are environmental conservation and life sustainability.